2016
DOI: 10.1097/hjh.0000000000000876
|View full text |Cite
|
Sign up to set email alerts
|

Kidney CLC-K chloride channels inhibitors

Abstract: The SRA-36 molecule represents a new potential therapeutic option for hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Given that the stria vascularis is not protected from systemic circulation by the blood-cochlear-barrier (Jahnke, 1975) this implies that great care has to be taken when considering CLC-K blockers as potential diuretic drugs in the treatment of hypertension (Imbrici et al, 2014; Liantonio et al, 2016). On the other hand, this peculiarity makes the systemic application of activators of CLC-K/barttin (Zifarelli et al, 2010) or drugs enhancing folding and trafficking of barttin (Nomura et al, 2013) for treating sensorineural deafness possible.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the stria vascularis is not protected from systemic circulation by the blood-cochlear-barrier (Jahnke, 1975) this implies that great care has to be taken when considering CLC-K blockers as potential diuretic drugs in the treatment of hypertension (Imbrici et al, 2014; Liantonio et al, 2016). On the other hand, this peculiarity makes the systemic application of activators of CLC-K/barttin (Zifarelli et al, 2010) or drugs enhancing folding and trafficking of barttin (Nomura et al, 2013) for treating sensorineural deafness possible.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the kinetics and reversibility of inhibition (Extended Data Figures 3, 4), we reasoned that AK-42 is likely binding to the extracellular side of channel pore. Docking of AK-42 to the extracellular side of the CLC-2 model preferentially places this ligand near the outer vestibule of the ionpermeation pathway, in a similar site to that targeted by anionic inhibitors in CLC-Ka 35,36 . Notably, we found that AK-42 does not dock to the cryo-EM structure of CLC-1 (6COY) 45 , in line with our functional studies on selectivity ( Figure 2C).…”
Section: Ak-42 Selectivity Specificity and Binding Sitementioning
confidence: 99%
“…Commercially available Cl --channel inhibitors 29 lack potency, with mid-µM to mM concentrations required to achieve inhibition of Clcurrent 9,30-32 .These molecules also generally lack selectivity against the different types of Clchannels, which strictly limits the usefulness of these compounds for cellular and organismal studies. For the CLC channels, the most potent and selective small-molecule inhibitors are those targeting CLC-Ka, one of two CLC homologs expressed in the kidney [33][34][35][36] . For CLC-2, the only reported small-molecule (non-peptide) inhibitors require application of high concentrations (~1 mM) 9,10,24,37 .…”
mentioning
confidence: 99%
“…However, due to expression of ClC-K/barttin channels in both the kidney and inner ear, it will be difficult to develop specific drugs without undesirable side effects. Recently, while testing new benzofuran derivatives designed to block ClC-K function, Liantonio et al (2016) described the most potent and selective ClC-K blocker discovered to date (SRA-36). This compound is able to inhibit not only wild-type channels, but also the Cl - currents of polymorphic ClC-K channels associated with hypertension (Liantonio et al, 2016).…”
Section: Mammalian Clcs and Human Disordersmentioning
confidence: 99%
“…Recently, while testing new benzofuran derivatives designed to block ClC-K function, Liantonio et al (2016) described the most potent and selective ClC-K blocker discovered to date (SRA-36). This compound is able to inhibit not only wild-type channels, but also the Cl - currents of polymorphic ClC-K channels associated with hypertension (Liantonio et al, 2016). Although several studies have made significant progress on the identification of compounds modulating ClC-K channel function (Liantonio et al, 2004, 2006, 2016; Picollo et al, 2004), there are not yet therapeutic drugs available.…”
Section: Mammalian Clcs and Human Disordersmentioning
confidence: 99%